Open access repositories a global perspective with an emphasis on library and information science subject - Janen, T.; Rathinakumar, K. (University of Jaffna, 2018)
Directory of Open Access Repositories (DOAR) is an authoritative directory of academic open access repositories. It provides a quality – assured listing of open access repositories around the world. DOAR harvest and assign metadata to allow categorization and analyses to assist the wider use and exploitation of repositories. This paper highlights the growth and development of open access repositories on Library and Information Science (LIS) subject area handled by various organizations which were registered under DOAR database. The study explores various aspects of open repositories and tries to present their overall development with respect to (LIS). Also it provides a detail description of repositories in terms of continent, country, organization, software, repository types, repository operations, operational status, most frequent content type, frequent language and growth of the open DOAR database with respect to LIS subject area. The result shows that European continent maintain large number of repositories for LIS, within this continent, United States has high number of repositories. Journal articles and thesis and dissertation are the highly used content type among all counties, also most of the repositories. Hold multi content type. DSpace (42.6%) and E-Print are the widely used software to develop repositories. English was the most frequently used language for the open access repositories. This study shows status of LIS subject repositories all around the world and its awareness among the LIS organization to develop repositories for the different kind of users.
Keywords: institutional repositories; Open access repositories; Library and information science